ENGLISH AND UZBEK NEWSPAPER HEADLINES: A COMPARATIVE PRAGMATIC STUDY - G. Mirzayeva,; D. Qurbonmuratova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This  article  studies  pragmatic  features  of  English  and  Uzbek  newspaper headlines. The article focuses on brevity, source marking, numbers, evaluation, and the way a headline guides the reader's interpretation before the article is read. The material includes a small comparative corpus of recent headlines from Reuters, The Guardian, and Gazeta. uz, and Xalq So'zi, supported by earlier headline research. Comparative analysis, pragmatic analysis, and close discourse reading are used in the study. The analysis shows that English headlines often rely on stronger compression, contrast, and short  attention  signals,  while  Uzbek  headlines  often  place  more  explanation  and institutional  framing  inside  the  headline  line  itself.  Both  traditions  use  numbers, authority, and cause-and-effect wording to create trust and urgency. The article may be useful for comparative pragmatics, media studies, translation, and classroom work with authentic news language.